Andaleeb Al-Amad College for Nursing and Midwifery - AbdulSalam, Kareem; Nammari, Murad; Johari, Saif (My University, 2018)
This project involves a redesign process for Al-Hajja Andaleeb Al Amad College for Nursing and Midwifery which is managed and operated by Arab Women Union Society and located in the North mountain- Nablus-Palestine. The analysis of the building has been done adopting the concept of Post Occupancy Evaluation (POE) for buildings, which is usually done to evaluate the building in operation stage. The analysis of the existing buildings’ design has covered all design disciplines covering architectural, structural, mechanical, electrical, safety and environmental fields. Accurate data has been produced based on survey questionnaires that has been given to different users such as administrative staff, teaching staff, students, and the board of the society. which gave the beneficiaries the chance to present their opinion, explain they needs if any, of the building after being in operation for around 3 years, also the use of several computer programs that are known to be used for analytical studies in different disciplines, thus giving us a clear and comprehensive idea about design, operation & other issues that might need intervention that will be redesigned in this part of project. Thus, enriching the old design that has been analyzed in the first phase of the project. Based on the above and considering the purpose of the evaluation done, there will be a possibility to present some improvements on the design covering all above-mentioned aspects and taking into consideration the standard requirements of the concerned ministries like Ministry of Health & Ministry of Education & Higher Education for such projects. Our project will emphasize on most of engineering aspects including Architectural, Structural, Mechanical, Electrical, and environmental systems. Local and international standards and codes of practice will be applied. by the end of this project, it can be implemented as a college with best design conditions regarding engineering disciplines towards occupants’ comfort.